Design Web-Based Attention System Using RFID - Dias Sugiarto; Mudofar Baehaqi; Erfan Subiyanta (Fakultas Teknik Universitas 17 Agustus 1945 Cirebon, 2022)
Absence is an activity of reporting and recording attendance in an institution, based on how it is used, the manual attendance system carried out in tertiary institutions requires students to fill out an attendance form with a signature during lectures. These deficiencies can be overcome by utilizing technology combined with the RFID system. An attendance system using web-based RFID is a system that utilizes RFID (Radio Frequency Identification) technology to record individual attendance. This system is designed by utilizing hardware in the form of RFID readers and tags, as well as software and network infrastructure. The software used in this attendance system will receive attendance data from the RFID reader and store it in a database. The attendance data can be accessed through a web interface that can be accessed by administrators or authorized users. This web interface will display individual attendance information, such as date, check-in time, and check-out time. In addition, the system can also provide periodic attendance reports or upon request. This web-based RFID attendance system provides convenience in recording individual attendance. Users no longer need to use manual methods such as attendance cards or attendance lists. By using RFID tags, the process of recording attendance can be done automatically and efficiently.